Compact NMR spectroscopy for real-time monitoring of a biodiesel production. (1st January 2015) - Killner, M.H.M.; Garro Linck, Y.; Danieli, E.; Rohwedder, J.J.R.; Blümich, B.
Graphical abstract: Highlights: On-line monitoring of a transesterification reaction by compact 1 H NMR spectroscopy. Developed PLS models from NMR-spectra recorded at 1 T to monitor biodiesel conversion. Real-time observation of methanol partitioning between glycerol and oleic phases. Resonance frequency of hydroxylic MeOH protons used to predict the conversion ratio. Abstract: The use of biodiesel shows innumerous advantages compared to fossil fuels, since biodiesel is a biodegradable and non-toxic fuel. Nowadays, most of the biodiesel commercialized in the world is produced by the transesterification reaction of vegetable oils with methanol and basic catalysis. Understanding the reaction kinetics and controlling its optimum progress for improving the quality of the final product and to reduce production costs is of paramount importance. The present work explores compact 1 H NMR spectroscopy to follow the course of the transesterification reaction in real time. For this purpose the magnet is integrated into a flow setup which allows one to transport the neat solution from the reactor into the measurement zone and back again into the reactor. A multivariate calibration model applying Partial Least Squares regression was built to analyze the measured data and to obtain information about the biodiesel conversion ratio with errors on the order of 1%. This information is used in combination with a Lorentzian deconvolution of the spectra to estimate the relative concentrations of methanol present in the ester-rich phase in comparison with the one in the glycerol phase, the second medium involved in the reaction mixture. Finally, we demonstrate that the conversion ratio can also be monitored by measuring the chemical shift of the hydroxylic protons of methanol and glycerol present in the ester-rich phase. These results demonstrate that a compact NMR spectrometer can provide spectra with good quality and time resolution suitable for real time quality control of biodiesel production.